Use of Sham Interventions in Randomized Controlled Trials in Neurosurgery - Gorayeb, Rodrigo Panico; Forjaz, Maria João; Ferreira, António Gonçalves; Ferreira, Joaquim José (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background The use of sham interventions in randomized controlled trials (RCTs) is essential to minimize bias. However, their use in surgical RCTs is rare and subject to ethical concerns. To date, no studies have looked at the use of sham interventions in RCTs in neurosurgery.Methods This study evaluated the frequency, type, and indication of sham interventions in RCTs in neurosurgery. RCTs using sham interventions were also characterized in terms of design and risk of bias.Results From a total of 1,102 identified RCTs in neurosurgery, 82 (7.4%) used sham interventions. The most common indication for the RCT was the treatment of pain (67.1%), followed by the treatment of movement disorders and other clinical problems (18.3%) and brain injuries (12.2%). The most used sham interventions were saline injections into spinal structures (31.7%) and peripheral nerves (10.9%), followed by sham interventions in cranial surgery (26.8%), and spine surgery (15.8%). Insertion of probes or catheters for a sham lesions was performed in 14.6%.In terms of methodology, most RCTs using sham interventions were double blinded (76.5%), 9.9% were single blinded, and 13.6% did not report the type of blinding.Conclusion Sham-controlled RCTs in neurosurgery are feasible. Most aim to minimize bias and to evaluate the efficacy of pain management methods, especially in spinal disorders. The greatest proportion of sham-controlled RCTs involves different types of substance administration routes, with sham surgery the less commonly performed.
Keywords: randomized controlled trials; neurosurgery; bias; sham